2011
DOI: 10.1089/jamp.2010.0833
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Allergen Challenge in Allergic Children: Continuous Increase of Nitric Oxide in Exhaled Air 72 Hours After Allergen Inhalation Independent of Bronchial Obstruction

Abstract: An increase in FeNO in sensitive subjects starts a few hours later than the decrease in FEV(1). Consequently, measurements of FeNO seem to be useful in long-term monitoring of the allergic reaction triggered by a specific allergen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(29 reference statements)
4
7
1
Order By: Relevance
“…This observation is consistent with previous studies that used common [14][15][16]26] and occupational allergens [27,28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation is consistent with previous studies that used common [14][15][16]26] and occupational allergens [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…The kinetics of changes in FeNO after BAC has been assessed at different time points in several studies. In patients with positive asthmatic responses, FeNO was elevated starting from the eighth hour postchallenge onward, and it was still elevated 48 [33] and 72 h after the BAC [16]. In patients with dual asthmatic responses, the maximal FeNO increase has been reported to be 10 h after challenge [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the patients with physician-diagnosed asthma and four subjects with negative SPT were excluded from further analyses. The median age of the remaining 73 subjects with AR was 24 years (range 13-44); the median age of the 20 healthy control subjects was 23 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Subjectsmentioning
confidence: 99%
“…Recent studies have shown that the continuous increase of FeNO in exhaled air 72 hours after allergen inhalation in grass pollen-sensitive participants is independent of the bronchial obstruction observed 32. Most occupational studies, however, obtained the last measurement of FeNO 20–24 hours after allergen challenge,23–27 while the maximum increase in FeNO occurred 48 hours after allergen challenge with Dermatophagoides pteronyssinus in atopic participants with dual asthmatic responses 10 33.…”
Section: Discussionmentioning
confidence: 99%